Fullerene and fullerene-aluminum nanostructured films as sensitive layers for gas sensors - Grynko, D.; Burlachenko, J.; Kukla, O.; Kruglenko, I.; Belyaev, O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The responses of quartz crystal microbalance (QCM) sensors coated by
fullerene and fullerene-aluminum films to ethanol and water vapors are investigated. The
possibility of controlling the adsorption properties of such films by inserting the
aluminum and by ultraviolet irradiation that changes the film morphology in a definite
way is demonstrated.